Gender Reckonings: New Social Theory and Research - Messerschmidt, James W; Messner, Michael A; Connell, Raewyn; Martin, Patricia Yancey (NYU Press, 2018)
Vivid narratives, fresh insights, and new theories on where gender theory and research stand today Since scholars began interrogating the meaning of gender and sexuality in society, this field has become essential to the study of sociology. Gender Reckonings aims to map new directions for understanding gender and sexuality within a more pragmatic, dynamic, and socially relevant framework. It shows how gender relations must be understood on a large scale as well as in intimate detail. The contributors return to the basics, questioning how gender patterns change, how we can realize gender equality, and how the structures of gender impact daily life. Gender Reckonings covers not only foundational concepts of gender relations and gender justice, but also explores postcolonial patterns of gender, intersectionality, gender fluidity, transgender practices, neoliberalism, and queer theory. Gender Reckonings combines the insights of gender and sexuality scholars from different generations, fields, and world regions. The editors and contributors are leading social scientists from six continents, and the book gives vivid accounts of the changing politics of gender in different communities. Rich in empirical detail and novel thinking, Gender Reckonings is a lasting resource for students, researchers, activists, policymakers, and everyone concerned with gender justice.